CKD-506, a novel HDAC6-selective inhibitor, improves renal outcomes and survival in a mouse model of systemic lupus erythematosus. Issue 1 (December 2018) - Choi, Eun; Song, Ji; Ha, Nina; Choi, Young; Kim, Sungjoo
Abstract Systemic lupus erythematosus (SLE) is a chronic multisystemic autoimmune disease with an unknown etiology. Recently, it has been elucidated that dysregulated histone deacetylase (HDAC) activity is related to the pathogenesis of inflammatory and autoimmune diseases. Broad-spectrum HDAC inhibitors are effective for the treatment of allergy, cancer, and autoimmune diseases, but they have several adverse side effects. Thus, the purpose of this study was to evaluate the effects of a novel HDAC 6-specific inhibitor, CKD-506, in a murine SLE model. CKD-506 significantly improved survival rate and significantly decreased the incidence of severe proteinuria, blood urea nitrogen, kidney inflammation, and glomerular infiltration of IgG and C3. In addition, CKD 506 reduced the proportions of CD138+ plasma cells, CD4− CD8− T cells, and CD25+ cells and the Th1/Th2 ratio in the spleen. CKD-506 significantly reduced inflammatory cytokines such as IL-10, IL-15, IL-17, TNF-α, and IFN-inducible protein (IP-10) and significantly increased TGF-β in serum. CKD-506 also significantly reduced IFN-γ, IL-1β, IL-4, IL-6, IP-10, MCP-1, and CCL4 levels in kidney. CKD-506 decreased the production of various pro-inflammatory cytokines and chemokines in the serum and kidneys, resulting in inhibition of cell migration and suppression of lupus nephritis without adverse effects.